Higher Stomatal Density Improves Photosynthetic Induction and Biomass Production in Arabidopsis Under Fluctuating Light - Sakoda, Kazuma; Yamori, Wataru; Shimada, Tomoo; Sugano, Shigeo S.; Hara-Nishimura, Ikuko; Tanaka, Yu (Frontiers in Plant Science, 2020)
Stomatal density (SD) is closely associated with photosynthetic and growth characteristics in plants. In the field, light intensity can fluctuate drastically within a day. The objective of the present study is to examine how higher SD affects stomatal conductance (gs) and CO2 assimilation rate (A) dynamics, biomass production and water use under fluctuating light. Here, we compared the photosynthetic and growth characteristics under constant and fluctuating light among three lines of Arabidopsis thaliana (L.): the wild type (WT), STOMAGEN/EPFL9-overexpressing line (ST-OX), and EPIDERMAL PATTERNING FACTOR 1 knockout line (epf1). ST-OX and epf1 showed 268.1% and 46.5% higher SD than WT (p < 0.05). Guard cell length of ST-OX was 10.0% lower than that of WT (p < 0.01). There were no significant variations in gas exchange parameters under theat steady state between WT and ST-OX or epf1, although these parameters tended to be higher in ST-OX and epf1 than WT. On the other hand, ST-OX and epf1 had showed a faster response of A induction compared with than WT after step increase in light because of owing to the higher gs under initial dark condition., while In addition, ST-OX and epf1they showed initially faster gs induction and, at the later phase, slower gs inductionhad a slower or similar response of gs. Cumulative CO2 assimilation in ST-OX and epf1 was 57.6% and 78.8% higher tended to be larger than WT attributable to faster photosynthetic A induction with no reduction of water use efficiency (WUE)., epf1 yieldeding 25.6% higher biomass than WT under fluctuating light (p < 0.01). In the present study, higher SD resulted in faster photosynthetic induction owing to the higher initial value of gs. epf1, with a moderate increase in SD, achieved greater biomass production than WT under fluctuating light with no penalty on WUE. These results suggest that higher SD can be beneficial to improve biomass production in plants under fluctuating light conditions.